PENGGUNAAN MEDIA PAPAN KANTONG UNTUK MEMOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV UPT SDN 206 GRESIK - Sherli Rahayu, Sherli; Noviardani Kartika Prameswari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pancasila Education learning in elementary schools still faces problems in the form of low student learning motivation due to the lack of variety of learning media used by teachers. The learning process tends to be dominated by lecture methods and the use of textbooks, so that students are passive and less actively involved. This study aims to describe the application of the Pancasila pocket board media and the learning motivation of fourth-grade students in Pancasila Education learning on the material of implementing rules in the surrounding environment. This study uses a descriptive qualitative approach with a case study type. The research subjects were 24 fourth-grade students of UPT SDN 206 Gresik. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the application of the Pancasila pocket board media has a positive impact on the learning process. The use of this media is able to create a more active, interactive, and enjoyable learning atmosphere. Students showed an increase in learning motivation marked by increased enthusiasm, activeness in discussions, courage to express opinions, and focus during the learning process. The pocket board media also helps students understand the material more concretely through manipulative activities and group collaboration. In addition, this media supports teachers in delivering material more creatively and innovatively. Thus, the Pancasila pocket board can be used as an effective alternative learning medium to increase student motivation and engagement in Pancasila Education in elementary schools.